DWI as a Quantitative Biomarker in Predicting Chemotherapeutic Efficacy at Multitime Points on Gastric Cancer Lymph Nodes Metastases. Issue 13 (March 2016) - Zhong, Jinman; Zhao, Weiwei; Ma, Wanling; Ren, Fang; Qi, Shun; Zheng, Jianmin; Wang, Xifu; Lv, Tianchu; Su, Zhanliang; Yin, Hong; Ren, Jing; Huan, Yi
Abstract : Abstract: The purpose of the hypothesis testing is to determine that apparent diffusion coefficient (ADC) as an early biomarker can predict the metastatic lymph nodes' (LNs) response to neoadjuvant chemotherapy in advanced gastric cancer (GC) in early stage. From March 2011 to June 2015, 106 patients with advanced GC were enrolled in the study. Patients underwent conventional magnetic resonance imaging and functional diffusion weighted imaging before and 3 days, 7 days, 30 days, and 60 days following the standard chemotherapy. After surgery, among 3034 detected LNs, the positive group was divided into complete response (CR) group, partial response (PR) group, and stable disease (SD) group in accordance to the Response Evaluation Criteria in Solid Tumors (RECIST) 1.1. Mean ADCs, short/long diameters of LNs before chemotherapy between the whole positive and the negative LNs were compared by t test. Changes of mean ADCs in 3 groups were analyzed by 1-way ANOVA. The mean ADC of the whole positive LNs was (1.145 ± 0.014) × 10 −3 mm 2 /s, which was significantly lower than that of the whole negative LNs ([1.491 ± 0.010] × 10 −3 mm 2 /s; P < 0.05). The means of both short/long diameters in the whole positive LNs were significantly longer than those in the whole negative LNs ( P < 0.05). In CR, PR, and SD groups, the mean ADC of metastatic LNs on the 3rd day, 7th day, 13th day, and 16th day following the chemotherapy were all higher than that of LNs before chemotherapy, respectively (all P < 0.05). In addition, significant difference was found between mean ADCs in any 2 time points (all P < 0.05), except between mean ADCs in the 3rd day and in the 7th day of the chemotherapy. In conclusion, ADC can be used as an early biomarker to predict the metastatic LNs' response to neoadjuvant chemotherapy in advanced GC in early stage.